Ameliorative Action Of Nigella Sativa Against Iron Induced Chromosomal Aberrations In Rat Bone Marrow Cells In Vivo - NUZHAT PARVEEN; G.G.H.A. SHADAB (International Journal of Pharma and Bio Sciences, 2011)
Iron deficiency is a worldwide problem and is, in general, more frequent than its excess. Nigella sativa may also act as an ROS scavenger and as a metal chelant. To examine these possibilities, we tested in vivo the effect of Nigella sativa (50 mg/kg b.wt.) against the genotoxicity of FeSO4.7H2O. Bone marrow cells were obtained from the rats using the technique described by Preston et al. (1987). The results of treatments with Nigella sativa indicated that it statistically significantly decreases the number of with aberrations induced by FeSO4.7H2O, but it cannot completely protect cells from damage. Nigella sativa showed the most efficient anticlastogenic effect during simultaneous treatment with FeSO4.7H2O. The result further strengthened the findings about the protective and antigenotoxic properties of Nigella sativa.